Основные вредители декоративных насаждений Донецкой области (2000–2009 гг.) и борьба с ними - Попов, Г.В. (Донецький ботанічний сад НАН України, 2009)
В статье приводятся данные об известной на сегодня фауне членистоногих, повреждающих декоративные растения зелёных насаждений Донецкой обл. За последние 10 лет зафиксирован один достоверный случай инвазии на территорию региона инорайонного вредителя (каштановая минирующая моль, Cameraria ohridella Deschka & Dimic, 1986) и только 9 видов заметно вредили. Предложены меры борьбы с ними. Up-to-date information on the known fauna of arthropoda that damages decorative plants in green plantations of
Donetsk region is presented in the article. One plausible case of invasion of an extrinsic pest (chestnut leafminer,
Cameraria ohridella Deschka & Dimic, 1986) of the territory has been recorded within the past 10 years and only
9 species have caused appreciable damage. Arrangements for pest control have been proposed.